Peningkatan Pemahaman Hukum dan Produktifitas Wakaf di Pimpinan Ranting Muhammdiyah Jogonegoro Kabupaten Magelang - Dakum; Nurwati; Ratih Setianingrum; Reasty Aprillia; Cahya Yoga Aditama; Febri Argo Kurniawan; Reza Maulana Ikhwan (Ilin Institute, 2020)
The purpose of this PKM is to provide counseling and assistance on improving the understanding of law and the productivity of waqf land at PKM partners in the Muhammadiyah Branch Leader of Jogonegoro, Mertoyudan District, Magelang Regency. The method used in this activity is counseling discussion and assistance to partners. The stages of this activity are making preparations at the beginning of the activity, followed by counseling about the ins and outs of waqf law and models of waqf productivity improvement, and the last is to provide assistance to partners in formulating a managed waqf productivity plan. The results obtained from this community service partner can increase understanding of the subtleties of waqf law and can make the distribution of waqf land management more productive for the prosperity of the people.